Coding theory and hyper BCK-algebras - Atamewoue Tsafack Surdive; Njeya Selestin; Lele C´elestin (Journal of Hyperstructures, 2018)
In this paper we define the notion of a hyper BCK valued function on a set and investigate some of it’s related properties as Y.B. Jun, S.Z. Song and C. Flaut have done for a BCK-algebras. We construct the codes generated by a hyper BCK valued function and provide an algorithm which allow to find a hyper BCK-algebra starting from a given binary block code. Moreover we establish the link between the hyper BCK-algebra constructed from a binary block code and hyper BCK-ideal on a hyper BCK-algebra.